Statistical analysis of meteorological factors and air pollution at winter months in elazi? Turkey - Akpinar, Ebru Kavak; Akpinar, Sinan; Öztop, Hakan Fehmi (Universidade Federal da Paraiba, 2009)
In the present study relationship between monitored air pollutant concentrations such as SO2 and the total suspended particles (TSP) data and meteorological factors such as wind speed temperature relative humidity and atmospheric pressure was investigated in months of October November December January February and March during the period of three years (2003 2004 and 2005) for Elazi{dotless}? city. According to the results of linear and non-linear regression analysis it was found that there is a moderate and weak level of relation between the air pollutant concentrations and the meteorological factors in Elazi{dotless}? city. © 2009 Journal of Urban and Environmental Engineering (JUEE). All rights reserved.
Keywords: Elazi{dotless}?; Meteorological parameters; Statistical analysis; Sulphur dioxide; Total suspended particles (TSP); Turkey; Winter months